89.9k views
3 votes
F(x) = x; translation

6 units down followed by a
vertical stretch by a factor
of 5
g(x) = 5x = 6

1 Answer

3 votes

Answer:

the transformed function becomes: g(x) = 5 x - 30

Explanation:

When the function f(x) = x is shifted down by a factor of 6 we have the following transformation:

f(x) --> x - 6

After this, a vertical stretch by a factor of 5 should affect the full functional expression in the following way:

5 ( x - 6) = 5 x - 30

Therefore the transformed function becomes: g(x) = 5 x - 30

User Preethi Rao
by
4.3k points